-4(x+6)-3=8-5x

Simple and best practice solution for -4(x+6)-3=8-5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(x+6)-3=8-5x equation:


Simplifying
-4(x + 6) + -3 = 8 + -5x

Reorder the terms:
-4(6 + x) + -3 = 8 + -5x
(6 * -4 + x * -4) + -3 = 8 + -5x
(-24 + -4x) + -3 = 8 + -5x

Reorder the terms:
-24 + -3 + -4x = 8 + -5x

Combine like terms: -24 + -3 = -27
-27 + -4x = 8 + -5x

Solving
-27 + -4x = 8 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
-27 + -4x + 5x = 8 + -5x + 5x

Combine like terms: -4x + 5x = 1x
-27 + 1x = 8 + -5x + 5x

Combine like terms: -5x + 5x = 0
-27 + 1x = 8 + 0
-27 + 1x = 8

Add '27' to each side of the equation.
-27 + 27 + 1x = 8 + 27

Combine like terms: -27 + 27 = 0
0 + 1x = 8 + 27
1x = 8 + 27

Combine like terms: 8 + 27 = 35
1x = 35

Divide each side by '1'.
x = 35

Simplifying
x = 35

See similar equations:

| 0=2x^2-7x+4 | | 9x+25+147=0 | | 28=x*16 | | 3-x=-6 | | 35x=16 | | 10t^2+33t-54=0 | | 2+5(x-3)-(-3+x)(2x+5)= | | 4y-8x=32 | | 9*3-4+27/9-2= | | 2(x+7)=6(-8) | | 28x=16 | | 62-7x=2x+20 | | 3x^2=2(x+2) | | -(-9y+3)-5=-5-y | | 41-6x=23 | | f(x)=4x-10 | | 2(0)=-2(0) | | x^2=27i | | 5x+6=66 | | 6y+20=-5+4y | | 2(x)=-2x | | 0.5x=2000 | | 66x-4x^2-272=0 | | 5x+6x+7x=180 | | f(x)=-7x+5 | | f(x)=-2x | | 5x+1=123 | | 4x^5-324x=0 | | f(x)=5x^2-12 | | 5a^3(25b-a)/a-25b | | 6w=7w-5 | | 4x+6=2x+6 |

Equations solver categories